Spectroscopic Properties and Computational Studies of Phosphosilicate-Doped Compounds Including (F, Cl, Br) - Rebaz obaid kareem; Othman Hamad; Hanifi Kebiroglu; Bast Mohammed (Journal of Chemistry Letters)
In this work, we added Cl, Br, and F atoms to the phosphate-silicate (PHS) molecule using the density functional theory (DFT) approach using a 6-31G basis set and the B3LYP level of theory. Numerous characteristics, including HOMO-LUMO, reduced density gradient (RDG), density of states (DOS), non-covalent interaction (NCI) theory, and molecular electrostatic potential (MEP) maps, were determined. The PHS molecule was found to have the biggest softness (0.330 eV-1) and electronegativity (5.117 eV), along with a lower energy gap (3.029 eV). These features point to improved inhibitor efficiency, polarizability, and higher chemical activity. On the other hand, it also implies that compounds with pure PHS are less stable when analyzed through the lens of density functional theory, which results in a greater degree of chemical reactivity.